PROSPECTS FOR USAGE OF ALTERNATIVE SOURCES FOR OBTAINING ELECTRIC POWER IN ISLAMIC REPUBLIC OF IRAN - D. B. Zorov; R. A. Zinovkin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper briefly describes the current state of power engineering industry  in the  Islamic Republic of Iran, contribution to gross output of electric power of gas turbine  power stations, combined-cycle power stations, hydroelectric power stations, wind power stations and solar power stations.  Substantiation of prospects pertaining to further development of alternative energy sources  in  the  Islamic Republic of Iran  in the context of availability of natural resources, economic efficiency and ecological safety